2020
DOI: 10.1007/s11085-020-10014-7
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Oxidation in Dry and Humid Atmospheres of the Equiatomic CrMnFeCoNi and CrCoNi High- and Medium-Entropy Alloys

Abstract: Surface degradation phenomena of two model equiatomic alloys from the CrMnFeCoNi alloy system were investigated in 2% O2 and 10% H2O (pO2 = 0.02 and 10−7 atm, respectively) at 800 °C for times up to 96 h. The crystallographic structures, morphologies, and chemical compositions of the corrosion layers developing on CrMnFeCoNi and CrCoNi were comparatively analyzed by mass gain analysis, X-ray diffraction, and scanning electron microscopy combined with energy-dispersive X-ray spectroscopy and electron backscatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…The differences in type and structure of the manganese oxide observed can mainly be explained by the low oxygen partial pressure p O2. When comparing different past studies, it can be concluded that the observed phases Mn 3 O 4 and Mn 2 O 3 are stable at much higher p O2 , e.g., p O2 = 0.02 atm and 10–7 atm in the study by Stephan‐Scherb et al, [ 16 ] compared to the p O2 = 2 × 10 −36 atm used in this study. However, the high diffusivity of manganese and its affinity for oxidation dominates the oxidation and corrosion process.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…The differences in type and structure of the manganese oxide observed can mainly be explained by the low oxygen partial pressure p O2. When comparing different past studies, it can be concluded that the observed phases Mn 3 O 4 and Mn 2 O 3 are stable at much higher p O2 , e.g., p O2 = 0.02 atm and 10–7 atm in the study by Stephan‐Scherb et al, [ 16 ] compared to the p O2 = 2 × 10 −36 atm used in this study. However, the high diffusivity of manganese and its affinity for oxidation dominates the oxidation and corrosion process.…”
Section: Resultssupporting
confidence: 50%
“…After exposure to 0.5% SO 2 for 6 h at 600 °C, the fcc grain structure is still clearly visible, but the entire CrMnFeCoNi surface appears oxidized (Figure 1a). The grains, sized on average 50 μm in diameter, [ 16 ] reveal a gray oxide layer with dark gray precipitates (region 1). Along the grain boundaries, mainly dark gray (region 2, about 10 % in area) and partly white precipitates have formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The equiatomic face-centered cubic (FCC) CrMnFeCoNi alloy, the so-called Cantor alloy [1] , is a model high-entropy alloy (HEA) that has received considerable interest in, e.g. , materials science and engineering [2][3][4][5] , diffusion [6,7] , corrosion/oxidation [8][9][10][11] , and electrocatalysis [12] . Due to its good malleability [13][14][15] , which made it the pioneering HEA to be thermomechanically processed and investigated in bulk form, and interesting mechanical properties at cryogenic temperatures, e.g.…”
Section: Introductionmentioning
confidence: 99%